Characteristics and Physical Fitness Levels of Students in Wetlands - Herita Warni; Syamsul Arifin; Ramadhan Arifin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the level of physical fitness and characteristics of students in the wetland area of Banjar Regency, South Kalimantan. The research method used is a survey method with descriptive analysis, namely data collection in the form of data on report cards for physical education lessons and interviews related to parents' income and school conditions. The study concluded that the physical fitness status of students in the wetland area in Banjar Regency, South Kalimantan was of good status but there were also students who had sufficient scores. In this sufficient category, the learning process for Physical Education, Sports and Health is constrained by ups and downs, extreme weather and field conditions that do not support activities or movements in learning.